2019
DOI: 10.1002/jcb.29332
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the complex regulatory relationships related to gastric cancer from lncRNA‐miRNA‐mRNA network

Abstract: The oncogenesis and progression of gastric cancer are closely correlated with the complex regulatory relationships among messenger RNA (mRNA), long noncoding RNA (lncRNA), and microRNA (miRNA). After constructing the gastric cancer lncRNA‐miRNA‐mRNA regulatory network, we analyzed the network topology properties and found that lncRNA ADAMTS9‐AS2 and C20orf166‐AS1 and miRNA hsa‐mir‐204 are key nodes. Further functional enrichment analysis and survival analysis were performed on these key nodes and the RNAs inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…The lncRNA NKX2‐1‐AS1 was identified to be highly expressed in primary lung adenocarcinomas and found to be associated with lung carcinoma cell migration [13]. Furthermore, bioinformatics studies have revealed that NKX2‐1‐AS1 may act as a competing endogenous RNA (ceRNA) in GC [14]. However, the contribution of aberrant expression of NKX2‐1‐AS1 in GC tumorigenesis and its prognostic relevance in GC remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA NKX2‐1‐AS1 was identified to be highly expressed in primary lung adenocarcinomas and found to be associated with lung carcinoma cell migration [13]. Furthermore, bioinformatics studies have revealed that NKX2‐1‐AS1 may act as a competing endogenous RNA (ceRNA) in GC [14]. However, the contribution of aberrant expression of NKX2‐1‐AS1 in GC tumorigenesis and its prognostic relevance in GC remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of how GRM3 takes impact on TMB is still unclear at present. As for THSD7B and FLNC , it has been reported that they are associated with tumor progression and/or prognosis of multiple tumors, such as NSCLC, 51 gastric cancer, 52 and hepatocellular carcinoma, 53 where the mechanism is still a mystery. It is worth exploring other potential mechanisms of how these genes impact immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…and Liu cohort 17 consisted of 110, 64, and 144 patients, respectively. In the Allen cohort,52.7% (58/110) was at the normal level of LDH, whereas 43.6% (48/110) was elevated. Overall the median TMB was 6.9 mutations per Mb.…”
mentioning
confidence: 90%
“…Mounting evidence demonstrates that lncRNA acts as a sponge for miRNA to regulate the level of target miRNA in human cancers. 31 For example, LncRNA PTCSC3 targeted miR-574-5p to decrease the level of miR-574-5p in cervical cancer. 32 We next used the bioinformatics analysis tool starBase to predict the potential targets of TMPO-AS1, and found that TMPO-AS1 was able to bind to miR-498.…”
Section: Discussionmentioning
confidence: 99%